Perbandingan Pendidikan Indonesia dan Mesir (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This study describes the contemporary education system in the Republic of Egypt. Since the revolu-tionary era of 1952, Egypt has sought to expand access to education opportunities for the commu-nity as a prerequisite for the country's social and economic development. In this study, a literaturereview was conducted to obtain and describe Egyptian educational information based on references from various sources. The results show that Egypt has an education system with two parallel struc-tures, namely the secular structure and the religious structure of Al-Azhar. The secular structure isregulated by the ministry of education while the religious structure of Al-Azhar by the ministry of Al Azhar affairs or commonly referred to as the ministry of religion in other countries. In the de-scription of this article, it can be seen the similarities and differences between the education systemin Egypt compared to Indonesia. Each country's education system has advantages and disad-vantages, so the two countries can take each other's best practices to be adopted and taken intoconsideration in the development of the education system.